EDUKASI PERBAIKAN POSISI DUDUK UNTUK STASIUN KERJA PELAYANAN PASIEN MENGGUNAKAN METODE RAPPID UPPER LIMB ASSESSMENT - Sri Rahayuningsih; Silvi Rushanti Widodo; Naufa Aulia Rahma; Rosa Andinar Bintang M; Afi Aprillia Putri; Willie (Universitas Kadiri, 2025)
One of the key factors in analyzing job effectiveness is the posture of employees within an organization. If a worker's posture is comfortable and good, and incorporates good ergonomics, then the results will be positive, and vice versa. Musculoskeletal disorders are a common problem experienced by workers worldwide related to ergonomics in the workplace, specifically affecting a worker's endurance during activities or tasks. This problem is common in any company where employees engage in uncomfortable, repetitive activities or movements. The main results obtained from the analysis in the patient service section were able to optimize and realize the use of ergonomic chairs to help workers at the Ngasem Kediri Health Center, East Java, to serve patients. The introduction of this ergonomic chair was carried out in 1 month by comparing the old working position with the new working position using this ergonomic chair. By making a comparison after using the chair and before using the chair, whether the complaints experienced by the workers were reduced or not. It is hoped that with this ergonomic chair, the workers at the Ngasem Kediri Health Center, East Java, can do their work comfortably and of course effectively and efficiently, which is expected to increase work enthusiasm and increase productivity at the Ngasem Kediri Health Center, East Java.